PENGARUH KUALITAS PELAYANAN, TINGKAT SUKU BUNGA DAN PENDAPATAN NASABAH TERHADAP PENGAMBILAN PINJAMAN DI KSP TONDONEGORO PURWODADI KABUPATEN GROBOGAN - Putri, Egidia Ananda; Kasidin, Kasidin (Universitas Of Surakarta, 2022)
The study purposes was determined the effect of service quality, interest rates and customer income on taking loans at KSP Tondonegoro Purwodadi Grobogan Regency. The research type is a survey and used data collection techniques through the distribution of questionnaires, interviews, observations and literature studies with 85 respondents. While the data analysis method used the analysis of research instruments consisting of validity test, reliability test, classical assumption test, multiple linear regression test. The research results showed that the service quality variable had a positive and significant effect on taking loans at KSP Tondonegoro Purwodadi Grobogan Regency, interest rates had a positive and significant effect on taking loans at KSP Tondonegoro Purwodadi Grobogan Regency, and customer income had a positive and significant effect. significant effect on taking loans at KSP Tondonegoro Purwodadi Grobogan Regency.